Inflammatory bowel diseases and the low-FODMAP diet: benefits and challenges in therapy - Skoracka, Kinga; Ratajczak-Pawłowska, Alicja Ewa; Marciniak, Martyna; Rychter, Anna Maria; Szwarc, Klara; Łykowska-Szuber, Liliana; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Nutrition, 2025)
Inflammatory bowel disease (IBD) is a chronic condition characterized by periods of exacerbation and remission, during which patients experience a range of gastrointestinal symptoms that negatively impact their quality of life. With the rising prevalence of the Crohn’s disease (CD) and ulcerative colitis (UC), new therapeutic approaches, including nutritional strategies, are being sought to support therapeutic treatment. One of dietary strategy under investigation is a diet low in fermentable oligosaccharides, disaccharides, monosaccharides and polyols diet (LFD), which limits the intake of indigestible and slowly absorbed carbohydrates. An increasing number of studies indicate that the LFD may alleviate visceral hypersensitivity and improve patients’ quality of life. However, alongside these benefits, the diet carries risks, particularly in regard to potential adverse effects on the gut microbiota and the possibility of vitamin and mineral deficiencies. The current body of evidence indicates that the LFD is best considered as a short-term therapeutic option for IBD patients in remission with persistent IBS-like symptoms. While there is evidence to suggest that it is effective in controlling symptoms, there is absence of data demonstrating that it reduces intestinal inflammation. Therefore, its use requires careful management to mitigate risks related to nutritional status and gut microbiota.